Soluble urokinase plasminogen activation receptor - An emerging new biomarker of cardiovascular disease and critical illness - Cyrille, Nicole B. (Ann Card Anaesth, 2016)
Soluble urokinase plasminogen activation receptor (suPAR) is an emerging new biomarker, which has been shown to not only correlate with traditional biomarkers but also outperform CRP at prognosticating CVD. More clinical trials on suPAR is in the future research agenda.